1999
DOI: 10.1016/s0008-6363(99)00207-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased hypoxic stress decreases AMP hydrolysis in rabbit heart

Abstract: While AMP hydrolysis to adenosine is prominent in early ischemia and acts to preserve cellular energy potential, during a second ischemic period, nucleotides are conserved by the stable inhibition of AMP hydrolysis. Furthermore, during 10% flow conditions, nucleotides are conserved, possibly via an IMP-accumulatory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This agrees with a study on AMPD in muscle of hibernating mammals that found that substrate affinity was reduced at low temperatures in the torpid state [ 16 ]. AMPD was also inhibited in rabbit heart experiencing hypoxia [ 34 ]. In that study, AMP deamination was high early in the ischemic period, and this served to preserve the AEC.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with a study on AMPD in muscle of hibernating mammals that found that substrate affinity was reduced at low temperatures in the torpid state [ 16 ]. AMPD was also inhibited in rabbit heart experiencing hypoxia [ 34 ]. In that study, AMP deamination was high early in the ischemic period, and this served to preserve the AEC.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of AMP is another factor influencing the degradation of nucleotides. Its conversion to adenosine by cytosolic 5′‐nucleotidase (5NT) or to IMP by AMP deaminase determines the degree of nucleotide degradation and ATP resynthesis during reoxygenation 38. In the deeply hypothermic rat, the accumulation of brain AMP during asphyxia begins with a conspicuous lag (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MgADP might be degraded further (Allen et al 1985) by the myokinase reaction. The calculation of [MgADP] i during ischaemia is not straightforward (Ingwall, 1987) because creatine kinase (Ventura‐Clapier & Veksler, 1994), myokinase (Golding et al 1995) and other enzymes involved in the catabolic processes (Gustafson et al 1999) are all sensitive to ischaemic metabolites. Recent data on intact skeletal muscle fibres suggest that [MgADP] i may reach levels high enough to induce marked alterations in cross‐bridge kinetics (Westerblad et al 1998).…”
Section: Discussionmentioning
confidence: 99%